Chemical compositions of the jackfruit juice (Artocarpus) cultivar J33 during storage - Shamsudin, Rosnah; Chia, Su Ling; Chin, Nyuk Ling; Muda @ Omar, Noraziah; Hassan, Osman (Asian Network for Scientific Information, 2009)
Chemical properties such as pH, total acidity, Total Soluble Solid (TSS) and sugar content changes during ripening of jackfruit cultivar J33 were evaluated at ambient temperature (±27°C; 70-80% RH). There are significant changes pH, total soluble solids, total acidity and sugar content at different ripening days. In this study, data obtained suggests that the ripening process of jackfruit cultivar J33 was at its optimum at day 9 after harvest at ambient temperature. The results will help to make the best use of jackfruit for different purposes and applications.